Managing Federal Workers' Compensation Injuries and Costs. (March 2015) - Mallon, Timothy M.; Grizzell, Tifani; Holland, Leslie; Hodgson, Michael
Abstract : Background: Federal Employees' Compensation Act injury rates and claim costs benefit from injury prevention and case management efforts. The Department of Labor Protecting Our Workers and Ensuring Reemployment data on lost time injuries and illnesses do support injury prevention and case management activities. Methods: The management efforts of the Department of Defense, Veterans Administration, and Department of Labor were examined to determine whether more is needed to support injury prevention and case management efforts. Results: Data on Protecting Our Workers and Ensuring Reemployment goal 3 metrics should be provided to safety and occupational health (SOH) personnel to support injury prevention and case management efforts. Discussion: Injury prevention and case management data need to be made available to SOH team members to prevent injuries and lower claims costs. Conclusion: Actionable information must be provided to SOH that will facilitate case management and injury prevention programs and lower costs.